2005
DOI: 10.1074/jbc.m410104200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization in Vitro of All Two-component Signal Transduction Systems from Escherichia coli

Abstract: Bacteria possess a signal transduction system, referred to as a two-component system, for adaptation to external stimuli. Each two-component system consists of a sensor protein-histidine kinase (HK) and a response regulator (RR), together forming a signal transduction pathway via histidyl-aspartyl phospho-relay. A total of 30 sensor HKs, including as yet uncharacterized putative HKs (BaeS, BasS, CreC, CusS, HydH, RstB, YedV, and YfhK), and a total of 34 RRs, including putative RRs (BaeR, BasR, CreB, CusR, HydG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
401
1
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 404 publications
(429 citation statements)
references
References 41 publications
19
401
1
8
Order By: Relevance
“…5). This is consistent with a recently published study of in vitro transphosphorylation tested for all possible combinations of E. coli histidine-sensor kinases and response regulators, which reported that phosphotransfer could occur between ArcB and RssB (Yamamoto et al 2005). However, RssB could also be phosphorylated by the chemotaxissensor kinase CheA, which seems of questionable physiological relevance in view of the highly dynamic CheA phosphorylation and dephosphorylation operating on a millisecond-to-second time scale (Sourjik 2005).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…5). This is consistent with a recently published study of in vitro transphosphorylation tested for all possible combinations of E. coli histidine-sensor kinases and response regulators, which reported that phosphotransfer could occur between ArcB and RssB (Yamamoto et al 2005). However, RssB could also be phosphorylated by the chemotaxissensor kinase CheA, which seems of questionable physiological relevance in view of the highly dynamic CheA phosphorylation and dephosphorylation operating on a millisecond-to-second time scale (Sourjik 2005).…”
Section: Discussionsupporting
confidence: 69%
“…5D,E). This raises the question of whether one response regulator can allosterically affect phosphotransfer from a sensor kinase dimer to another response regulator, even though its own phosphorylation is less efficient (or even absent, as suggested by the interference of RssB with in vitro phosphotransfer in several other twocomponent systems, as reported by Yamamoto et al 2005). Such biochemical details and physiological implications of protein interactions and phosphotransfer reactions in two-component networks, in particular if they consist of phosphorelay systems, will have to be clarified in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This process of pathway insulation following duplication has resulted in extant organisms harboring large sets of two-component pathways that can transduce signals without significant cross-talk [4,11,40]. Consistently, an examination of the specificity residues in two-component proteins from an individual organism typically reveals significant differences in almost all possible pairwise comparisons of kinases or regulators [37].…”
Section: Evolution Of Two-component Signaling Specificitymentioning
confidence: 94%